Epidemiological profile of uterus cancer in Bahia (2015-2019) (Research, Society and Development, 2022)
Objective: to characterize the epidemiological profile of cervical cancer in Bahia between the years 2015 to 2019. Methodology: this is a study with a quantitative, descriptive approach of cases with positive cytology results for cervical cancer, identified from Pap smear tests, registered in the Cancer Information System and available at the Informatics Department of the Unified Health System, between the years 2015 to 2019. Results: the years with the lowest and highest number of Pap smear tests were 2015 and 2019, respectively. A tracking coverage of 32.0% was found for the years 2017 to 2019. The number of altered exams showed a slight increase in the period analyzed. As for the previous performance of cytology, it was identified that 81% of women had already performed it before, 11% underwent the exam for the first time, 7% with this information ignored. Intervals between 1 year and 2 years for the examination prevailed. Tracking was the main reason for performing the exam. The education variable is greatly underreported. Invasive squamous cell carcinoma was the most frequent (68.30%), followed by In Situ adenocarcinoma (16.49%) and invasive adenocarcinoma (15.21%). The most affected age group was 35-44 years (31.1%). Conclusion: the high number of altered results suggests that the implementation of proactive policies is emerging so that the prevention and early diagnosis of cervical cancer is significantly minimized. Studies with this design are important tools for identifying the real epidemiological situation, providing opportunities for better decision-making.